Transmission of vocational skills in the second part of careers: the effect of ICT and management changes - Nathalie Greenan; Pierre-Jean Messe (Journal for Labour Market Research, 2018)
This paper looks at the effect of technological and organisational changes on the probability for workers in the second part of their careers of transmitting their knowledge to other colleagues in their employing firm. We use matched employer-employee data to link changes occurred at the firm level with knowledge transmission behaviours measured at the individual-level. To control for selection bias based on differences in observable characteristics between workers employed in changing work environments and those employed in non-changing ones, we apply propensity score matching techniques. We find that ICT and management changes reduce significantly the probability for workers over 45 of transmitting their knowledge to their colleagues. Then, we analyse the role of training in mitigating this negative impact. To address issues of self-selection into training, we use propensity score matching methods and a proxy for unobservable productivity. We show that participation in a training program regarding ICT tools may help older workers restore their role of knowledge transmitters.
Keywords: J14; J24; 330; Older workers; Knowledge transmission; Skill obsolescence